(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This monograph aims at analyzing the relation of the activities of the program NER/UDESC This monograph aims at analyzing the relation of the activities of the program NER/UDESC with social entrepreneurship. In the course of this investigation, we realized that the interdisciplinary of the aforementioned office favors a social, integrating view, which amalgamates the academic knowledge of teaching with the activities of university extension. These, in turn, reverberate in the communities, fulfilling its important social function of academic training and feedback of this knowledge to society. It’s important to highlight that these activities are part of eight different areas university extension; also, they are carried out with people of all age groups in several regions of Brazil. Thus, they exemplify and justify social entrepreneurship (which has been growing since the 1990s), characterized by social responsibility, since social entrepreneurs do not aim at profit but, rather, at the collective well-being.